Collagenous Colitis Mucosa Is Characterized by an Expansion of Nonsuppressive FoxP3+ T Helper Cells. Issue 9 (15th December 2020) - Daferera, Niki; Escudero-Hernández, Celia; Nyström, Sofia; Jenmalm, Maria C; Hjortswang, Henrik; Ignatova, Simone; Ström, Magnus; Münch, Andreas
Abstract: Background and Aim: Increased frequencies of T regulatory (Treg) cells, key players in immune regulation, have been reported in inflammatory bowel diseases, including collagenous colitis (CC). However, traditional Treg identification techniques might have misinterpreted the frequencies of Treg cells in CC. Thus, we investigated the presence of genuine Treg cells in CC. Methods: Treg cells were analyzed in mucosal and peripheral blood samples of CC patients before and during treatment with the corticosteroid drug budesonide and in healthy controls. Samples were analyzed by flow cytometry by classifying CD3 + CD4 + cells as activated FoxP3 high CD45RA - Treg cells, resting FoxP3 dim CD45RA + Treg cells, and nonsuppressive FoxP3 dim CD45RA - T helper cells. Traditional gating strategies that classified Treg cells as CD25 high CD127 low, FoxP3 + CD127 low, and CD4 + CD25 + FoxP3 + were also used to facilitate comparison with previous studies. Results: Activated and resting Treg cell frequencies did not change in active CC mucosa or peripheral blood and were not affected by budesonide treatment. Instead, nonsuppressive FoxP3 dim CD45RA - T helper cells were increased in active CC mucosa, and budesonide helped restore them to normal levels. In contrast, traditional Treg cell gating strategies resulted in increased Treg cell frequencies in active CC mucosa. No alterations were found in peripheral blood samples, independently of patient treatment or gating techniques. Conclusion: Previously reported increase of Treg cells is a result of incomplete Treg phenotyping, which included nonsuppressive FoxP3 dim CD45RA - T helper cells. Because budesonide did not affect Treg percentage, its therapeutic effect in CC might involve alternative mechanisms.